Szkockie referendum niepodległościowe jako przykład dążeń secesjonistycznych w Europie - Hankus, Przemysław (Instytut Studiów Międzynarodowych Uniwersytetu Wrocławskiego, 2015)
The article discusses the issue of secessionist aspirations in Europe, focusing on the case of Scotland’s aspirations for independence manifested in the course of the referendum on independence that was held on the 18th of September 2014 in Scotland. While analysing reasons and consequences of the Scottish plebiscite th eauthor ponders the future of Scotland, taking into account demands of the ruling Scottish National Party (SNP) and political philosophy of libertarianism on the one hand and signalizes possible versions of carrying out secession according to the will of people who inhabit these areas, where pro-secessionist demands are supported by the majority of the society members, on the other hand
Keywords: Szkocja; referendum; niepodległość; secesja